2002
DOI: 10.1143/jjap.41.1643
|View full text |Cite
|
Sign up to set email alerts
|

Domain Wall Displacement Detection Mini Disc with Land/Groove Recording Applied to Mini Disc Systems

Abstract: The development reported herein is that of a surface micromachining technology using two SU-8 layers as a structural material. Three different processes are presented and discussed: the first process makes use of a sol-gel as the sacrificial layer; the second process utilizes the SU-8 itself as the sacrificial layer; the third process utilizes silicon dioxide as the first sacrificial layer and the sol-gel as the second sacrificial layer. These three processes are adapted for one structural layer structure. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Since the invention, many related studies have been reported. Fujita et al realized a capacity of 2.0 GB on a 64 mm disc with land/groove recording [2]. They developed a substrate optimizing deep groove geometry in order to obtain a sufficiently wide recording power tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the invention, many related studies have been reported. Fujita et al realized a capacity of 2.0 GB on a 64 mm disc with land/groove recording [2]. They developed a substrate optimizing deep groove geometry in order to obtain a sufficiently wide recording power tolerance.…”
Section: Introductionmentioning
confidence: 99%